PARTICULARITIES OF PARLIAMENTARY OVERSIGHT IN DIFFERENT POLITICAL REGIMES - Silvia-Claudia CĂLIN-MIHALCEA (Challenges of the Knowledge Society, 2015)
The quality and intensity of the parliamentary oversight performed over the Government are shaped by several major criteria: political regime, electoral system, structure of the Parliament (unicameral/bicameral), parliamentary culture and tradition. This paper emphasizes some distinctive elements and particular mechanisms of the control exercised over the activities of the executive power, from the point of view of the political regime established in states with modern democracies.